A ZrNiAl related high-pressure modification of CeRuSn. Issue 36 (18th August 2016) - Niehaus, Oliver; Heymann, Gunter; Huppertz, Hubert; Rodewald, Ute Ch.; Chevalier, Bernard; Matar, Samir F.; Hoffmann, Rolf-Dieter; Pöttgen, Rainer
Abstract : Monoclinic CeRuSn with its own structure type transforms to a high-pressure modification at 11.5 GPa and 1470 K (1000 t press, Walker type module). Abstract : Monoclinic CeRuSn with its own structure type transforms to a high-pressure modification at 11.5 GPa and 1470 K (1000 t press, Walker type module). The structure of the high-pressure phase was refined from X-ray single crystal diffractometer data at room temperature. The HP-CeRuSn subcell structure adopts the ZrNiAl type: P 6̄2 m, a = 751.4(3) and c = 394.6(2) pm, w R 2 = 0.0787, 310 F 2 values and 15 variables. The Ru2 atoms within the Sn6 trigonal prisms show a strongly enhanced U 33 parameter. Weak satellite reflections indicate a commensurate modulation: (3 + 1)D superspace group P 31 m (1/3, 1/3, γ )000, a = 751.4(3) and c = 394.6(2) pm, γ = −1/3, w R 2 = 0.0786, 1584 F 2 values, 32 variables for the main reflections and w R 2 = 0.3757 for the satellites of 1 st order. A description of this new superstructure variant of the ZrNiAl type is possible in a transformed 3D supercell with the space group R 3 m and Z = 9. The driving force for formation of the modulation is strengthening of Ru–Sn bonding within the comparatively large Ru@Sn6 trigonal prisms. Electronic structure calculations point to an almost depleted Ce 4f shell. This is substantiated by temperature-dependent magnetic susceptibility data. Fitting of the data within the interconfiguration fluctuation model (ICF) resulted in cerium valences of 3.41 at 10 K and 3.31 at 350 K. Temperature dependent specific heat data underline the absence of magnetic ordering.